Perancangan dan Penerapan Sistem Inventory Barang pada Toko Big Store Padang dengan Menggunakan Bahasa Pemrograman Java dan MYSQL - Dimas Dwi Randa (INTECOMS: Journal of Information Technology and Computer Science, 2018)
During the Big Store clothing store doing inventory data processing his shirt still manually by recording ordinary that takes a long time to recalculate the amount of stuff that is in the barn. Then be made to an application program which helps and facilitates the shop owners in calculating its inventory. Applications created using the Java programming language and the MySQL database as its storage medium. The method used is the EOQ method, which allows the owner to store EOQ method in minimizing inventory costs so that the owner can increase sales revenue at minimum cost. Keywords : Java, EOQ, UML, MySQL